2016
DOI: 10.1080/17518253.2016.1258088
|View full text |Cite
|
Sign up to set email alerts
|

Microwave synthesis and fluorescence properties of homo- and heterodimeric monomethine cyanine dyes TOTO and their precursors

Abstract: A series of monomeric and dimeric cyanine dyes belonging to the thiazole orange family have been prepared via an improved synthetic procedure, by the reaction of the monomethine dye containing an iodoalkyl group with tertiary diamine linkers under microwave irradiation. The effects of microwave power and irradiation time on yield were examined. The electronic absorption and steady-state fluorescence spectra of prepared dyes have been investigated. Fluorescence properties indicate significance in singlet oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…The increase in the quantum yield of the T state of MCD in complexes with biomolecules may be of importance for using these dyes as potential candidates in photodynamic therapy (similarly to MCD synthesized earlier [ 73 ]). In the case of MCD 1 – 3 , triplet dye molecules will be formed only in a complex with a biomolecule, which imparts to these dyes targeted characteristics when used in photodynamic therapy.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the quantum yield of the T state of MCD in complexes with biomolecules may be of importance for using these dyes as potential candidates in photodynamic therapy (similarly to MCD synthesized earlier [ 73 ]). In the case of MCD 1 – 3 , triplet dye molecules will be formed only in a complex with a biomolecule, which imparts to these dyes targeted characteristics when used in photodynamic therapy.…”
Section: Resultsmentioning
confidence: 99%
“…The authors suggest avoiding the use of two quaternary precursors, which reduces the number of steps. Monocationic and dicationic MCDs of the TO family were prepared by the thioalkyl method under solvent-free microwave irradiation by condensation of benzothiazolium salts with quaternary quinolone salts having a reactive methyl group in the presence of triethylamine [15]. This method was used in a recent work [8] for the synthesis of symmetrical MCDs with various terminal heterocyclic groups and substituents at nitrogen atoms.…”
Section: Synthesis Of Mcdsmentioning
confidence: 99%
“…For the synthesis of homodimeric MCDs having 4 positive charges, the following scheme is known (Figure 8) [25]: In [26] the synthesis of new dimeric MCDs based on the TO chromophore under the action of microwave radiation was described. The synthesis is performed via the reaction of a monomethine dye having an iodoalkyl group with tertiary diamine linkers.…”
Section: Synthesis Of Mcdsmentioning
confidence: 99%
“…A new series of oxindole sensitizers (29)(30)(31)(32)(33) were designed and synthesized under microwave irradiation [24]. These exhibited respectable photoelectric conversion efficiencies due to excellent electron-donating triphenylamine (TPA) donor and the thiophene in the spacer and are differentiated by various halogensubstituted oxindole acceptors.…”
Section: Microwave Synthesized Dyes/sensitizers In Dsscsmentioning
confidence: 99%
“…Likewise, the condensation of benzothiazole with quarternary salts of quinoline which upon coupling with the tertiary diamine linkers gave tetracationic analogous (bis-intercalators) of monomethine cyanine dyes 45. The steady-state fluorescence spectral studies of 45 revealed greater labeling affinity toward DNA and proved for singlet oxygen sensitization property, and found to be a potential candidate for photodynamic therapy [32].…”
Section: Cyanine Dyesmentioning
confidence: 99%